Penggunaan Bahasa Madura dalam Keluarga Muda Etnik Madura Di Kabupaten Sumenep Madura - A. Erna Rochiyati Sudarmaningtyas (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
This research was conducted in Sumenep Madura, particularly in suburb and in Kepanjen. The objectsin this research are young families who are Madurese ethnic that use Madurese language (BM). Theresults show that in general, young families no longer dominate the ethnic Madurese very subtle level BM(bhasa tengghi), even if it could be just a little and even then not in accordance with the rules of the BMboth grammatical structure and diction. Similarly, in correspondence, they never write in BM. However,the language is very controlled BM subtle level variance (bhasa Engghi Bhunten / EB) and a variety ofcoarse language (taq bhasa / Mapas / Engghi -Enten/EE). The diversity of language acquisition because itis used in everyday communication verbally, especially in the internal family, but communication betweenthe child (especially a child who is still a child ) and parent, grandparent, grandmother using Indonesianlanguage (BI) or BI and BM mixture. BM is used in the range of coarse (taq bhasa) .